The Genomic Health of Human Pluripotent Stem Cells: Genomic Instability and the Consequences on Nuclear Organization - Henry, Marianne P.; Hawkins, J. Ross; Boyle, Jennifer; Bridger, Joanna M. (Frontiers in Genetics, 2019)
Human pluripotent stem cells (hPSC) are increasingly being used for cell-based regenerative therapies worldwide; with embryonic and induced pluripotent stem cells as potential treatments for debilitating and chronic conditions, such as age-related macular degeneration, Parkinsons disease, spinal cord injuries and type 1 diabetes. However, with the level of genomic anomalies stem cells generate in culture, their safety may be in question. Specifically, hPSCs frequently acquire chromosomal abnormalities, often with gains or losses of whole chromosomes. This review discusses how important it is to efficiently and sensitively detect hPSC aneuploidies, to understand how these aneuploidies arise, consider the consequences for the cell, and indeed the individual to which aneuploid cells may be administered.